Dosage and Duration of Methylprednisolone Therapy Affect the Occurrence of Cushing Habitus in Patients with Systemic Lupus Erythematosus - Didi Permana; Melisa I Barliana; Laniyati Hamijoyo (Wolters Kluwer Medknow Publications, 2019)
Context: Systemic lupus erythematosus (SLE) is a multisystem disease with very diverse developments. Corticosteroid is mostly used for the treatment of SLE as antiinflammatory and immunosuppressant, but its long-term use and high dose can cause the side effects such as Cushing habitus. Aim: Analyze the risk factors of Cushing habitus occurrence in patients with SLE comprising pulse dose, duration of therapy, daily dose, and total dose of methylprednisolone. Settings and Design: Case Control study. Materials and Methods: 40 patients with SLE treated at Rheumatology outpatient clinic at Hasan Sadikin Hospital in Bandung was conducted. Each of these patients were divided into case and control groups. The design of this study was a case control study, the data was retrieved from medical record of patients with and without cushing habitus. Statistical Analysis: Chi-squared test was used to test the relationship between independent variables followed by linear logistic regression analysis to determine the influence of the most influential variable in causing Cushing habitus. Results: The results of this study showed that the use of total dose of methylprednisolon (> 8040 mg) has a significant effect on the incidence of Cushing habitus p = 0.029; odds ratio [OR] = 3.55). In addition, daily dose of methylprednisolone >9.4 mg has a significant effect on Cushing habitus (p = 0.012; OR = 2.98). Conclusion: Significant relationship between daily dose and total dose of methylprednisolone on the occurrence of Cushing.